Web application: Tele-education using web real-time communication (WebRTC) / Zulfikri Paidi and Wan Muhammad Aizuddin Wan Roslan - Paidi, Zulfikri; Wan Roslan, Wan Muhammad Aizuddin (UiTM Cawangan Perlis, 2017)
Distance learning can be described as the process of learning between lecturers and students from different locations over the Internet. This paper discusses about a web based video call application using Web Real-Time Communication (WebRTC). It allows lecturers and students to communicate in a real time through the web application for learning purposes. The web application enables users to perform a video call using web browser. However, sometimes the lecturers are not able to attend a class due to unforeseen circumstances. So, they need to find a suitable time to make a replacement class and gather all students to perform a video conference. With the availability of this web application, both students and lecturers can just make a replacement class through video conference. Besides, some students are usually busy with their activities and they do not have time to consult or make appointment with their lecturers. This video call application helps to address the problem by connecting both students and lecturers from different places through a web application. The objectives have been identified, which are to design and develop a web based video call application using WebRTC and to evaluate the performance and functionality of the web application. The result is gathered based on the test conducted, which shows that users will experience a smooth video streaming by using wireless LAN as compared to the broadband, which causes a sluggish video streaming.